Real-time rendering : computer graphics with control engineering - Wong, Gabriyel (Automation and control engineering., 2014)
This book presents a model-based control technique where the control system design (PID-based) is derived from a data driven process. It describes this data-driven model estimation technique using the System Identification Methodology on the rendering process which provides better accuracy than techniques in other research. The book introduces the reader to the concepts of how control systems work with real-time computer graphics through relatively easy to understand content.